(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
There is a broad consensus that Argentina must deepen its integration in the world economy, though less agreement exists on the specific objectives and mechanisms to achieve it. In particular it is necessary to diversify and improve the “quality” of the export basket, while simultaneously provide time and assistance to the sectors that require adapting their business to be able to compete in a more open economy. In a scenario characterized by a heterogeneous local productive structure, integration strategies must address the different realities of each activity in terms of the gap to the international frontier, the characteristics of dominant incumbent agents, markets morphologies and forms of competition, among other factors. These strategies must consider the expected impacts not just on foreign trade, but also on the dynamics of productivity and technological change, as well as on employment and income distribution. This article aims to contribute to the debate on these issues through the elaboration of a “policy board” that identifies both, the different components of available strategies for different types of sectors, as well as the possible interactions and hierarchies among the abovementioned components. It also provides ideas on the institutional conditions involved in the definition and implementation of a new strategy for Argentinaʼs integration in the world economy.